Kekuatan Karakter Mahasiswa di Tengah Pandemi Covid-19 - Hetti Sari Ramadhani; Jatie K. Pudjibudojo; Lena Panjaitan (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
The main challenge for educational institutions in the middle of the pandemic is fostering students to maintain character strengths in poor conditions. Various difficulties come quickly, such as changes in the online learning system, strict health protocols that apply to the threat of viruses that are scary all the time. Character strengths have a broad impact on life satisfaction, subjective well-being, friendly relationships, and academic success. This study aims to determine the condition of initial student character strengths, especially those who have just entered college, as positive traits used in dealing with changes during the COVID-19 pandemic and contribute to the development of character strengths theory. Peterson-Seligman. The research subjects were 145 students who filled out the 72-item VIA-IS scale online and analyzed using descriptive analysis. The results showed that most early students had high character strengths (68.3%) and responded to change by highlighting their signature strengths of kindness, humor, love, honesty, and gratitude. This research is expected to describe the strength of character as an effort to adapt to change in the middle of the covid-19 pandemic.